In Vitro Development of Enteric-Coated Tablets of the Probiotic Lactobacillus fermentum LF-G89: A Possible Approach to Intestinal Colonization - Spínello, Paola; do Nascimento, Pamela; da Silveira, Verônica C.; Staudt, Tatiana; Omidian, Hamid; Tissiani, Ana Caroline; Bertol, Charise Dallazem (Recent Advances in Drug Delivery and Formulation, 2024)
Background: Probiotics must be able to withstand the demanding environment of the gastrointestinal system to adhere to the intestinal epithelium, promoting health benefits. The use of probiotics can prevent or attenuate the effects of dysbiosis that have a deleterious effect on health, promoting anti-inflammatory, immunomodulatory, and antioxidant effects. Objective: The aim of the study was to prepare tablets containing Lactobacillus fermentum LF-G89 coated with 20% Acryl-Eze II® or Opadry® enteric polymers. Methods: Tablet dissolution was evaluated under acidic and basic pH conditions, and aliquots of the dissolution medium were plated to count the Colony-forming Units (CFU). The free probiotic's tolerance to pH levels of 1.0, 2.0, 3.0, and 4.0, as well as to pepsin, pancreatin, and bile salts, was assessed. Results: The probiotic was released from tablets coated after they withstood the pH 1.2 acid stage for 45 minutes. The release was higher with the Acry-Eze II® polymer in the basic stage. The amount of CFU of free probiotics at pH 1.0 to 4.0 as well as pepsin reduced over time, indicating cell death. Conversely, the CFU over time with pancreatin and bile salts increased, demonstrating the resistance of L. fermentum to these conditions due to hydrolases. Conclusion: Both coating polymers were able to withstand the acid step, likely ensuring the release of the probiotic in the small intestine, promoting colonization. Coating with enteric material is a simple and effective process to increase the survival of probiotics, offering a promising alternative to mitigate the negative effects of the dysbiosis process.
Keywords: L. fermentum